A simple method to improve the adsorption properties of drinking water treatment residue by lanthanum modification. (April 2019) - Wang, Changhui; Hao, Zheng; Wei, Zhao; Bai, Leilei; Yao, Zongbao; Xu, Huacheng; Jiang, Helong; Yan, Zaisheng; Zhao, Yuanyuan
Abstract: The loading of La can substantially enhance the adsorption capability of drinking water treatment residue (DWTR) for better recycling. Normally, the modification was based on incubation of DWTR and La solution at a certain ratio, following by solid-liquid separation and drying processes. This study attempted to simplify La loading procedures by adopting high ratio of DWTR and La solution to eliminate the solid-liquid separation, aiming to promote the potential actual production. According to the results of the short- (2 d) and long-term (30 d) P adsorption tests, the N2 gas sorption and desorption analysis, the X-ray photoelectron spectroscopy analysis, and the metal fractionation, the substantial enhanced adsorption capability of the modified DWTR was maintained and the La loading mechanisms to DWTR changed little after eliminating solid-liquid separation processes during modification; typically, La loading increased the initial P adsorption rates from 1.00 (raw DWTR) to 6.08 and 6.03 mg g −1 d −1 for the modified DWTR with and without the separation processes. Furthermore, the DWTR before and after modification had little unfavorable effect on the survival of snail Bellamya aeruginosa, while eliminating the separation processes tended to reduce the bioavailability of Al, Fe, and La in the modified DWTR. These results demonstrated that solid-liquid separation was not the key step for DWTR modification and that the developed simple modification method was feasible for La loading to DWTR, promoting the beneficial recycling in environmental remediation. Highlights: This study simplified a normal La loading process for DWTR modification. The substantial enhanced initial adsorption by modified DWTR was still achieved. The La loading mechanisms to DWTR by the simple method changed little. The Al, Fe and La bioavailability decreased in DWTR modified by the simple method.